Three essays on corporate finance - Yang, Endong (2018)
In the first chapter, we show that stock liquidity negatively affects firms’ corporate social responsibility (CSR) ratings. To identify the causal effect, we use the decimalization of stock trading as an exogenous shock to liquidity. The negative liquidity effect on CSR is more pronounced for firms with CEOs approaching the retirement age, firms with more analyst coverage, and firms with more short-term institutional ownership. These findings suggest that liquidity discourages firms’ investment in CSR activities through inducing managerial short-termism. Our findings reveal the real effect of stock liquidity as an important stock market characteristic on firms’ engagement in CSR activities and highlight a dark side of liquidity in exacerbating the conflict between shareholders and other stakeholders. In the second chapter, we examine how stock liquidity affects firms’ timeliness of loss recognition in financial reporting, namely, conditional accounting conservatism. Using both the 1997 liquidity shock and the 2001 decimalization as exogenous shocks to stock liquidity, we establish a negative causal effect of stock liquidity on accounting conservatism. Our results are robust to alternative measures of conservatism and various definitions of stock liquidity. The negative effect is more pronounced for firms with higher long-term institutional ownership, firms with stronger presence of blockholders and activists, firms with bank debt, and firms with higher CEO ownership. These findings suggest a substitution effect of stock liquidity on accounting conservatism. Namely, higher liquidity improves governance through facilitating threat of intervention and threat of exit for shareholders, and thus shareholders rely less on accounting conservatism as a governance mechanism. In the third chapter, we analyze the effects of government credit on export activities in China by merging the universal transaction-level data from China Customs and loan data from the China Development Banks (CDB). We find that CDB credit to SOEs leads to higher export amount of SOEs and lower export product varieties of private firms in the same industry. Moreover, CDB credit to upstream industries leads to higher export amount and more export destinations of private firms in downstream industries. This effect is not pronounced for SOEs in downstream industries. Infrastructure credit generally has positive effects on export activities for all types of firms. We use the pre-determined turnover timing of municipal politicians as an instrument for CDB loans. The results suggest government credit to upstream industries could have positive spillover effects on private firms in the downstream industries.